1998
DOI: 10.2134/jeq1998.00472425002700050030x
|View full text |Cite
|
Sign up to set email alerts
|

Sewage Sludge and Mycorrhizal Effects on Secar Bluebunch Wheatgrass in Mine Spoil

Abstract: Establishing vegetation on mine spoil often requires amendments to supply nutrients and microorganisms to re‐establish attributes associated with developed soil. Arbuscular‐mycorrhizal fungi (AMF) and composted sewage sludge (CSS) were evaluated as possible minespoil amendments to create a topsoil substitute for revegetation of the Midnite Mine, Stevens County, Washington. Most original topsoil was buried and existing spoil is low in nutrients and organic matter and not capable of supporting desired vegetation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 0 publications
1
10
1
1
Order By: Relevance
“…In these cultures the increased absolute (a% = 35) and relative (A% = 17) arbusculum richness indicated good functioning of the symbiosis (Table 4). The observed high rate of mycorrhizal infection of red fescue in our sewage sludge compost amended mine spoil is in contrast with results of Thorne et al (1998), who found reduced arbuscular mycorrhizal fungi colonization of Secar bluebunch wheatgrass grown in sewage sludge compost amended mine spoil.…”
Section: Metal Accumulation and Arbuscular Mycorrhizal Fungi Colonisacontrasting
confidence: 99%
“…In these cultures the increased absolute (a% = 35) and relative (A% = 17) arbusculum richness indicated good functioning of the symbiosis (Table 4). The observed high rate of mycorrhizal infection of red fescue in our sewage sludge compost amended mine spoil is in contrast with results of Thorne et al (1998), who found reduced arbuscular mycorrhizal fungi colonization of Secar bluebunch wheatgrass grown in sewage sludge compost amended mine spoil.…”
Section: Metal Accumulation and Arbuscular Mycorrhizal Fungi Colonisacontrasting
confidence: 99%
“…Arbuscular mycorrhizal fungi are able to exploit nutrients released by mineralization of organic matter. However, when applied in high concentrations, organic amendments such as manure, sewage sludge or compost can be harmful to arbuscular mycorrhizal fungi (Thorne et al 1998). Given this disparity, Gryndler et al (2008) assessed application of arbuscular mycorrhizal fungi and plant growth-promoting rhizobacteria to spoil bank clays to increase plant growth and compensate for reduced organic amendments.…”
Section: From Larney Et Al (2003a)mentioning
confidence: 99%
“…However, the establishment of a plant cover is only part of the reclamation process; creation of a self-sustaining ecosystem after revegetation practices is of equal importance (Pichtel et al, 1994). Amendment of mine spoils with sewage sludge and arbuscular mycorrhizal (AM) fungi will help to create a functional soil (Sabey et al, 1990;Thorne et al, 1998).…”
Section: Introductionmentioning
confidence: 99%